The Elementary Schools of the Danube Steamship Company in the Pecs Mining District (1868-1938/1944) - Huszar, Zoltan (Civilia, 2015)
This article aims to give an outline of the elementary school system that was adapted and supported by the Royal Danube Steamship Company /DSC; Erste k. k. priv. Donau-Dampfschiffahrts-Gesellschaft (DDSG); Elso cs. kir. szab. Dunagozhajozasi Tarsasag (DGT)/which got its footing in the Pecs coal basin in 1852, starting out with the description of the existing public school system of County Baranya and Hungary of the period discussed. The author highlights those revolutionary measures that were taken by the company in the field of education, covering reforms, school building activities and the different ways of financial and material support the company provided for its employees, including schoolmasters and school teachers. As a background, he gives a detailed picture of the social and political life that characterized Hungary in the end of the 19th and the first half of the 20th century, mentioning all the important names, acts and events that influenced the educational processes. The special value of the article is the detailed presentation of the everyday life on a mining colony, describing those activities, festive occasions and traditions that formed the lifestyle of the multinational community.The study is based on the author's own research conducted in Hungarian and Austrian archives and on published literature. His findings are expressed in simple but informative tables which are easy to overview. The excessive explanations in forms of footnotes and the long list of references offer opportunity for further research for those who are interested.
Keywords: DSC/DDSG; education in Hungary; Pecs; company culture